Antiplatelet and anticoagulant drugs management before gastrointestinal endoscopy: Do clinicians adhere to current guidelines?. Issue 1 (January 2015) - Bruno, Mauro; Marengo, Andrea; Elia, Chiara; Caronna, Stefania; Debernardi-Venon, Wilma; Manfrè, Selene Francesca; Musso, Alessandro; Puglisi, Flavia; Sguazzini, Carlo; Rizzetto, Mario; De Angelis, Claudio
Abstract Background Managing antiplatelet and anticoagulant drugs before endoscopy may be challenging. Aims To assess whether the pre-endoscopic management of antiplatelet/anticoagulant drugs is adherent to current guidelines and the influence of patients' characteristics, referring physician's specialty, type of endoscopic procedure and therapeutic regimen on adherence. Methods Two hundred and twenty patients taking aspirin, thienopyridines or warfarin and scheduled for upper endoscopy (± biopsies), variceal band ligation, colonoscopy (± biopsies or polypectomy), were prospectively analyzed. Results In 109 patients (49.5%) the management of antiplatelet/anticoagulant drugs was thoroughly compliant with guidelines. Neither demographic characteristics, nor in/outpatient status, nor type of endoscopic procedure, nor physician's specialty influenced the adherence but the therapeutic regimen had a significant impact (p < 0.0001) as compliance was less likely in patients on warfarin. Unwarranted drugs withholding was more frequent before colonoscopy than upper endoscopy (p = 0.0001). Warfarin was stopped longer than recommended more frequently than aspirin (p = 0.009). The International Normalized Ratio was properly checked before endoscopy in 47.7% of patients. Among the 55 patients who withheld warfarin, the decision about bridging to low molecular weight heparin was appropriate in 21 (38.2%). Conclusions Compliance with guidelines is low especially in the management of warfarin, both among gastroenterologists and other physicians.